Attempt to modify klebsiella carriage in ankylosing spondylitic patients by diet: correlation of klebsiella carriage with disease activity. Issue 2 (April 1984) - Shinebaum, R; Neumann, V; Hopkins, R; Cooke, E M; Wright, V
Abstract : Patients with ankylosing spondylitis were asked to follow a 'klebsiella exclusion diet' for 5 months of a 10-month study. The same percentage of faecal samples were positive for klebsiella whether the patients were on or off the experimental diet. The diet also failed to influence variability of klebsiella serotypes. We found no correlation between acquisition of klebsiella and deterioration of disease symptoms, as recorded by the patients. Furthermore, carriage of klebsiella did not correlate with any of the following parameters of disease activity measured in the outpatient clinic: morning stiffness, pain measured on a visual analogue scale, analgesic consumption, ESR, total serum IgA. We found no evidence, therefore, that faecal klebsiella is involved in disease exacerbations of ankylosing spondylitis.